Tuberculosis detection from raw sputum samples using Au-electroplated screen-printed electrodes as E-DNA sensor - Sharif, M. N.; Taufiq, S.; Sohail, M.; Abbas, S. R. (Frontiers in Chemistry, 2022)
Tuberculosis (TB) remains a leading cause of death globally, especially in underdeveloped nations. The main impediment to TB eradication is a lack of efficient diagnostic tools for disease diagnosis. In this work, label free and ultrasensitive electrochemical DNA biosensor for detecting Mycobacterium tuberculosis has been developed based on the electrodeposition of gold nanoparticles on the surface of carbon screen-printed carbon electrode (Zensors) for signal amplification. Particularly, screen-printed electrodes were modified by electrochemical deposition of Au to enhance the conductivity and facilitate the immobilization of ssDNA probes via Au-S bonds. The electrochemically modified SPEs were characterized using Scanning electron microscopy/Energy Dispersive X-Ray Analysis (SEM/EDX) and X-Ray Diffraction (XRD). Cyclic voltammetry (CV) and differential pulse voltammetry (DPV) techniques were used to investigate the DNA hybridization between single-stranded (ssDNA) probe and target DNA (tDNA). Under the ideal conditions, DPV exhibited a correlation coefficient R2 = 0.97, when analyzed with different tDNA concentrations. The proposed DNA biosensor exhibits a good detection range from 2 to 10 nm with a low detection limit of 1.91 nm, as well as high selectivity that, under ideal conditions, distinguishes non-complementary DNA from perfectly matched tDNA. By eliminating the need for DNA purification, this work paves the path for creating disposable biosensors capable of detecting DNA from raw sputum samples.